PELATIHAN DAN PENDAMPINGAN PEMASARAN DIGITAL PADA UMKM MUDEENA FOOD DI KOTA MAKASSAR - Andi Balqis Mutiara Asizah; Valentino Aris; Muhammad Taufik; Andi Ruslan; Muhammad Qardawi Hamzah; Sri Asmirani (LPPM Universitas Abdurrab, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in Indonesia’s economy, yet many still struggle to adapt to digital transformation, particularly in marketing and sales. This Community Service Program (PKM) partnered with Mudeena Food, a food-and-beverage MSMEs in Makassar, to train and mentor the implementation of digital marketing strategies via Instagram. The activities were designed in several stages, starting with needs analysis, training design, content production, mentoring and content dissemination, and evaluation. Over three months, the team helped develop a structured content plan, produce engaging visual and video materials, and manage Instagram features such as Feeds, Reels, and Stories. Performance data refer to Meta Analytics Dashboard for the most recent three-month period, extracted in September 2025. The results show substantial improvements: impressions increased by 411%, reach by 122.8%, content interactions by 937.3%, and profile visits by 221%; the partner’s account also gained 91 new followers. These outcomes compare very favorably with the previous period, which recorded interactions, reach, and visits at around 25%. These achievements confirm that consistent, creative content, supported by an appropriate strategy, can enhance brand awareness and audience engagement while opening opportunities for sales growth. Beyond quantitative outcomes, the program improved the partner’s digital literacy and skills, enabling more independent management of social media marketing. Thus, digital marketing training and mentoring for MSMEs not only drive visibility and competitiveness but also strengthen business sustainability in the digital era.